Eddy-driven transports in the Antarctic Circumpolar Current system - Viebahn, Jan (2012)
This PhD thesis consists of three research papers. The first research paper addresses crucial issues of the present climate change debate, namely the response of the meridional overturning circulation (MOC) of the Southern Ocean (SO) to decadal-scale trends in wind stress forcing, and the ability of up-to-date meso-scale eddy parameterisations to represent the corresponding changes in the eddy field in climate models. The results show that it is indispensable to incorporate the correct sensitivity of eddy field into climate models in order to reproduce the correct sensitivity of the MOC to wind stress and that up-to-date meso-scale eddy parameterisations are only partially successful. The second and third research papers are guided by a more conceptual perspective and focus on one of the most common diagnostics of the MOC: the concept of the MOC streamfunction. The second research paper clarifies the question: Is it possible to define a MOC streamfunction completely void of standing eddies? It is shown that the construction of a MOC streamfunction with an exactly vanishing standing eddy part has to be performed by zonal integration along depth-dependent horizontal isolines of time-mean density. The third research paper considers the two most common approaches to calculating MOC streamfunctions directly in Eulerian space, i.e. the series expansion of the residual-mean eddy streamfunction and the series expansion of the quasi-Stokes streamfunction, and discusses their limitations. Diese Dissertation besteht aus drei Forschungsartikeln. Der erste Forschungsartikel behandelt entscheidende Fragen der gegenwärtigen Klimawandel-Diskussion: Wie reagiert die meridionale Umwälzzirkulation (MOC) des Südlichen Ozeans (SO) auf dekadisch-skalige Trends im Windstress-Antrieb? Inwieweit ist es den gegenwärtigen Parameterisierungen von meso-skaligen Wirbeln möglich, die entsprechenden Veränderungen im Wirbelfeld in Klimamodellen wiederzugeben? Die Ergebnisse zeigen: Um die richtige Abhängigkeit der MOC vom Windstress zu ...